thing
Patent Information
- Application Number
- JP2023533957
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-08
- Filing Date
- 2021-11-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-11-09
Smart Images

Figure 0007936798000001 
Figure 0007936798000002 
Figure 0007936798000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an article, and more specifically to an article comprising a combination of a polyolefin polymer and a solvent-based lamination adhesive composition having recyclable properties. [Background technology]
[0002] To date, the use of plastic products, such as packaging materials for the packaging industry, has increased dramatically worldwide. Unfortunately, this increased demand for plastic products has led to a significant increase in plastic waste, as plastic products are discarded by consumers after use, and this plastic waste has a negative impact on the environment in many countries around the world. To mitigate or reduce the plastic waste problem, manufacturers have tried to produce plastic products that can be easily recycled and reprocessed into other subsequent plastic products after the original plastic product has been used for its intended purpose. However, the development of plastic products made entirely from recyclable materials has had limited success.
[0003] Typically, plastic products such as laminated film structures are composite structures made from a combination of various different materials, some of which are recyclable and some are not. For example, International Publication No. 201927527 discloses a recyclable laminated film structure made from all recyclable materials such as polyethylene. However, the laminated film structure in International Publication No. 201927527 also utilizes a barrier adhesive, and the barrier adhesive in International Publication No. 201927527 is not disclosed as being recyclable or having recyclable properties. Therefore, while International Publication No. 201927527 discloses that the laminated film structure itself is considered recyclable, it does not disclose that the barrier adhesive has recyclable properties or meets the criteria for recyclability. Conventional adhesives used to bond two polymer film substrates together are generally known to be incompatible with the polymer film substrates. Therefore, known film structures containing two incompatible component layers or incompatible adhesives cannot be recycled "as is" because the resulting recycled material will not function adequately in the process of manufacturing subsequent articles from the recycled material. Furthermore, since the film substrate layer components are not compatible with each other, if it is desired that such two-layer (or more) multi-component film structures containing different substrates and different adhesives be recycled by a converter, the converter must separate the layers from each other before recycling the layers / adhesives, which complicates, inefficient, and expensive the recycling process.
[0004] Therefore, it is desirable to provide a first plastic article comprising a combination of (1) at least one polyolefin polymer and (2) a solvent-based lamination adhesive composition having recyclable properties and being compatible with the polyolefin polymer, so that the first article can be reprocessed (recycled) after its original use to form a subsequent second plastic product having sufficient performance characteristics to be useful as a second plastic article for various applications. As a result, it is possible to avoid discarding the environmentally friendly first plastic article and increasing global plastic waste. [Overview of the project]
[0005] The present invention relates to an article comprising a combination of (a) at least one polyolefin polymer, such as a polymer in the form of a film, and (b) a solvent-based adhesive composition having recyclability. In some embodiments, the recyclability of the solvent-based adhesive composition is determined by reprocessing (recycling) the article with the solvent-based adhesive composition to form a reprocessed (recycled) article, and then the properties of the recycled article made from the original article having the solvent-based adhesive composition are measured against a control article without the solvent-based adhesive composition, which is reprocessed in the same manner as the recycled article. The original article of the present invention has recyclability if the recycled article made from the original article having the solvent-based adhesive composition shows a performance degradation of less than 40 percent (<) compared to the control article.
[0006] In some embodiments, the present invention includes a first article such as pellets, single-layer or multi-layer films, single-layer or multi-layer laminates, packaging materials, and molded products.
[0007] In some embodiments, the present invention includes a subsequent second article made from any one of the first articles described above. In some embodiments, the second article may be, for example, a plastic composite, a molded article, a laminated structure, an industrial film such as a shrinkable film or a stretch wrap film, or an agricultural film.
[0008] In some embodiments, the present invention includes a process for producing a first article having recyclable properties, comprising contacting together (a) at least one polyolefin polymer and (b) a solvent-based adhesive composition having recyclable properties.
[0009] Advantageously, the first article produced incorporating the above solvent-based adhesive composition can be subjected to a recycling process in accordance with current recyclability guidelines for the packaging industry. For example, by using the solvent-based lamination adhesive composition of the present invention, which is a polyester system, in combination with a polymer film structure such as a 2.25 gs / square meter (gsm) total polyethylene (PE) high-density polyethylene (HDPE) film, a film structure is provided that can be reprocessed to produce a new single-layer film having properties that show a <40% decrease in performance compared to a control film that is reprocessed in the same way without the addition of any adhesive. For example, a laminated structure produced using a solvent-based adhesive allows a converter to (1) directly mechanically reprocess the laminated structure as a whole without the need to separate the materials constituting the laminated structure, and (2) produce a new film from the reprocessed laminated structure, the new film having a sufficiently desirable performance range. [Modes for carrying out the invention]
[0010] Unless otherwise stated, implied by the context, or customary in the art, all parts and percentages are based on weight, all temperatures are in degrees Celsius (°C), and all test methods are current as of the filing date of this disclosure.
[0011] With respect to a first article having an adhesive, the terms “recyclable” or “recyclable” as used herein mean mechanically recyclable or recyclable, meaning that the first article having an adhesive can be mechanically reprocessed to produce a second article having a desired performance range, the second article having a performance degradation of at least <40% compared to a control article without adhesive and reprocessed in the same manner as the second article. Examples of test methods and guidelines for determining the recyclability of plastic articles can be found in, but are not limited to, the publications “Benchmark Polyethylene Film and Flexible Packaging Innovation Test Protocol, Film-B-01” (2018) and “PE Film Standard Laboratory Processing Practices,” and The Association of Plastic Recyclers (APR) document number FPE-P-00 (2020).
[0012] As used herein, the term “composition” refers to the materials comprising the composition, as well as the mixture of reaction products and decomposition products formed from the materials of the composition.
[0013] "Polymer" means a polymer compound prepared by polymerizing monomers, whether of the same or different types. Therefore, the general term polymer encompasses the terms homopolymer (used to refer to polymers prepared from only one type of monomer, under the understanding that trace amounts of impurities may be incorporated into the polymer structure) and interpolymer, as defined below herein. Trace amounts of impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. A polymer may be a single polymer, a polymer blend, or a polymer mixture containing a mixture of polymers formed in situ during polymerization.
[0014] As used herein, the term “interpolymer” refers to a polymer prepared by the polymerization of at least two different types of monomers. Thus, the collective term “interpolymer” includes copolymers (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0015] As used herein, the terms “olefinic polymer” or “polyolefin” mean a polymer comprising, on a basis of weight of the polymer, a majority of an olefin monomer, such as ethylene or propylene, in a polymeric form, and optionally comprising one or more comonomers.
[0016] As used herein, the term "ethylene / α-olefin interpolymer" refers to an interpolymer in which, in its polymerized form, the majority (e.g., greater than 50 mol% [mol%] [>]) of units derived from ethylene monomers and the remaining amount of units derived from one or more α-olefins. Typical α-olefins used in the formation of ethylene / α-olefin interpolymers are C3-C3. 10 It is an alkene.
[0017] As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer comprising, in polymeric form, a majority (>50 mol%) of ethylene monomer and α-olefin as only two types of monomers.
[0018] As used herein, the term "α-olefin" refers to an alkene having a double bond at the primary or alpha(α) position.
[0019] "Polyethylene (PE)" or "ethylene-based polymer" means a polymer containing more than half (more than 50 mol%) of units derived from ethylene monomer. This includes polyethylene homopolymers, ethylene / α-olefin interpolymers, and ethylene / α-olefin copolymers. Common forms of polyethylene known in the art include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (ULDPE), very low-density polyethylene (VLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), reinforced polyethylene, polyethylene elastomers, and polyethylene plastomers. These PE materials are generally known in the art. However, the following description may help in understanding the differences between some of these different PE resins.
[0020] The term “LDPE” may also be referred to as “high-pressure ethylene polymer” or “highly branched polyethylene,” and is defined as meaning that the polymer is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at a pressure greater than 14,500 pounds per square inch (psi) (100 megapascals [MPa]) using free radical initiators such as peroxides (see, for example, U.S. Patents 8,916,667, 8,871,887, 8,822,601, 9,228,036, and 9,765,160). LDPE resins typically have a weight of 0.916 grams per cubic centimeter (g / cm³). 3 ) ~0.935g / cm³ 3 It has a density within the range.
[0021] The term "LLDPE" includes both resins made using conventional Ziegler-Natta catalyst systems and chromium-based catalyst systems, as well as single-site catalysts including but not limited to bis-metallocene catalysts (sometimes referred to as "m-LLDPE"), constrained geometry catalysts (CGC), and molecular catalysts. The resins include linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. LLDPE contains fewer long chain branches than LDPE, and includes substantially linear ethylene polymers as further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those described in U.S. Patent No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent No. 4,076,698, and blends thereof (such as those disclosed in U.S. Patent No. 3,914,342 or U.S. Patent No. 5,854,045). LLDPE can be made via gas phase, liquid phase or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0022] The term "MDPE" refers to polyethylene having a density of 0.926 g / cm 3 ~0.940 g / cm 3 . "MDPE" is typically made using chromium catalysts or Ziegler-Natta catalysts, or using single-site catalysts including but not limited to bis-metallocene catalysts, constrained geometry catalysts and molecular catalysts, and typically has a molecular weight distribution ("MWD") of >2.5.
[0023] The term "HDPE" refers to polyethylene generally prepared using Ziegler-Natta catalysts, chromium catalysts, or single-site catalysts including but not limited to bis-metallocene catalysts and constrained geometry catalysts, and having a density of 0.940 g / cm 3 or more and at most 0.970 g / cm 3 .
[0024] The term "ULDPE" refers to polyethylene generally prepared using Ziegler-Natta catalysts, chromium catalysts, or single-site catalysts including but not limited to bis-metallocene catalysts and constrained geometry catalysts, and having a density of 0.880 g / cm 3 to 0.912 g / cm 3 .
[0025] "Polyethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin copolymer containing a uniform short-chain branching distribution that comprises units derived from ethylene and units derived from at least one C3 to C 10 α-olefin comonomer, or at least one C4 to C8 α-olefin comonomer, or at least one C6 to C8 α-olefin comonomer. The polyethylene plastomer / elastomer has a density from 0.870 g / cm 3 , or 0.880 g / cm 3 , or 0.890 g / cm 3 to 0.900 g / cm 3 or 0.902 g / cm 3 , or 0.904 g / cm 3 , or 0.909 g / cm 3 , or 0.910 g / cm 3 , or 0.917 g / cm 3It has a density up to [value]. Non-limiting examples of preethylene plastomers / elastomers include AFFINITY® plastomers and elastomers (available from Dow Chemical Company), EXACT plastomers (available from ExxonMobil Chemical), TAFMER® (available from Mitsui Chemicals), NEXLENE® (available from SK Chemicals Co.), and LUCENE® (available from LG Chem Ltd.), as well as mixtures thereof.
[0026] The terms “blend,” “polymer blend,” and similar terms mean a composition of two or more polymers. Such a blend may or may not be miscible. Such a blend may or may not be phase-separated. Such a blend may or may not contain one or more domain configurations, as determined by transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, but one or more layers of a laminate may contain a blend. Such a blend may be prepared as a dry blend, or formed in situ (e.g., in a reactor), as a molten blend, or by other techniques known to those skilled in the art.
[0027] Terms such as "adhesive contact" mean that one opposing surface of one layer and one opposing surface of another layer are in contact with each other and bonded together in such a way that one layer cannot be removed from the other without damaging the interlayer surfaces (i.e., the contacting facial surfaces) of both layers.
[0028] The terms “comprising,” “including,” and “having,” and their derivatives, are not intended to exclude the presence of any additional components, processes, or procedures, whether or not they are specifically disclosed. To avoid any doubt, all compositions claimed through the use of the term “comprising” may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated. In contrast, the term “consisting essentially of” excludes any other components, processes, or procedures from the scope of any subsequent description, except those not essential to operability. The term “consisting of” excludes any components, processes, or procedures not specifically described or listed.
[0029] An object of the present invention is to produce a first article from original components for use in a first application, and then, after the first article has been used, to reprocess the used first article as a whole (i.e., the used first article can be subjected to, for example, a recycling process) to directly form a second article from the reprocessed first article. The second article can then be used in another subsequent second application.
[0030] The first article comprises a combination of (a) at least one polyolefin polymer and (b) a solvent-based adhesive composition. Surprisingly, the solvent-based adhesive composition used in the first article has recyclable properties to be imparted to the first article, and thus, in some embodiments, the first article has been found to be recyclable and can be used to produce second articles for various other applications.
[0031] In some non-limiting embodiments, the first article of the present invention may include, for example, one or more of the following articles: pellets, films such as single-layer or multi-layer films, multilayer laminates, packaging products, etc. In some non-limiting embodiments, the second article of the present invention may also include, for example, one or more of the following articles: pellets, films such as single-layer or multi-layer films, multilayer laminates, packaging products, etc.
[0032] A polyolefin polymer, component (a), useful for producing the first article of the present invention, may contain one or more polyolefins. The first article may be, for example, a polyolefin film. Generally, the polymer portion of the film consists of at least 80% polyolefin polymer in one embodiment, at least 85% polyolefin polymer in another embodiment, and at least 90% polyolefin polymer in yet another embodiment. In one embodiment, the polyolefin polymer is at least one PE polymer. For example, polyethylene may include one or more of HDPE, LDPE, LLDPE, and mixtures thereof. The polyolefin film may be a single-layer or multi-layer film, and may be a stretched film stretched by a machine direction orientation (MDO) or biaxial orientation process. In another preferred embodiment, the polyolefin is polypropylene (PP), oriented PP (OPP), biaxially oriented PP (BOPP), and mixtures thereof. The non-polyolefin portion of the film may consist of a polymer such as poly(vinyl alcohol) (EVOH) or polyamide (e.g., nylon), a functionalized bonded polymer, and a compatibilizer as described in U.S. Patent No. 10,300,686.
[0033] A solvent-based adhesive composition useful for producing the first article of the present invention, component (b) may include one or more solvent-based adhesive compositions having the recyclability characteristics defined above. The solvent-based adhesive compositions are such that when the first article having the solvent-based adhesive composition is reprocessed (recycled), the first article having the solvent-based adhesive composition exhibits a performance degradation of less than 40% compared to a control first article without the solvent-based adhesive composition. Both the first article and the control first article are reprocessed and tested in the same manner to determine their respective recyclability characteristics.
[0034] As described above, the present invention can include a wide variety of first articles, such as films, laminates, or packaging. Therefore, as merely illustrative examples of the present invention, it is described herein with reference to preferred embodiments that are single-layer or multi-layer laminated structures, more specifically multi-layer laminated structures. However, it will be understood by those skilled in the art that many other articles can constitute first articles other than laminates, and that the present invention is not limited thereto.
[0035] In some embodiments, the present invention includes, for example, a multilayer laminated structure. In other embodiments, the present invention includes an adhesive lamination process for manufacturing a multilayer laminated structure, and in yet another embodiment, the present invention relates to a packaged article made using a multilayer laminated structure.
[0036] In one broader embodiment, the present invention includes a multilayer laminated structure as a first article that can be used to produce a laminated packaging material, which can then be recycled at the storefront for further processing. The multilayer laminate comprises a combination of at least two polyolefin layer substrates bonded together by a layer of the solvent-based adhesive composition described above. For example, the multilayer laminated structure comprises (i) at least a first polymer film web, such as a polyethylene (PE) film; (ii) at least a second polymer film web, which may be the same PE film as the first layer or a different material; and (iii) a layer of the solvent-based polyester-based laminating adhesive composition having the above-described recyclability for bonding the first and second polyolefin film webs together, wherein the layer of the solvent-based laminating adhesive composition is compatible with the first and second film layers, and the layer of the solvent-based laminating adhesive composition is located on at least one surface of the multilayer of the first and second film layers to bond the first and second film layers together. If desired, one or more other optional film layer substrates can be added to the laminated structure along with adhesives added between the layers to produce a multilayer laminated structure containing two or more layers.
[0037] The first polyolefin film web, which is component (i) used to produce the multilayer laminate of the present invention, may contain one or more polyolefins. For example, the first polyolefin web may contain one or more polyolefin layers such as HDPE, LDPE, LLDPE, MDO PE, BOPE, and mixtures thereof.
[0038] In one preferred embodiment, the polyolefin film web may include a stretched monolayer or multilayer PE film, prepared using either a mechanical or biaxial stretching process, which is bonded to a second layer.
[0039] In another preferred embodiment, the polyolefin film web may be a multilayer film comprising one or more layers of HDPE, LLDPE, and LDPE.
[0040] In yet another preferred embodiment, the polyolefin film web may be a PP film web or a BOPP film web.
[0041] In yet another preferred embodiment, the polyolefin film web is composed of at least 80% polyolefin polymer in one embodiment, at least 85% polyolefin polymer in another embodiment, and 90% polyolefin polymer in yet another embodiment. In this embodiment, non-polyolefin polymers such as EVOH and polyamide, as well as functional binding layers and compatibilizers, may be used, as described in U.S. Patent No. 10,300,686.
[0042] The thickness of the first polyolefin film web used to form the recyclable laminate of the present invention may be, for example, 10 microns (μm) to 150 μm in one embodiment, 15 μm to 100 μm in another embodiment, and 20 μm to 50 μm in yet another embodiment.
[0043] The second polyolefin film web, which is component (ii) used to produce the laminate of the present invention, may contain one or more polyolefins, which may be the same as or different from the first polyolefin film web. For example, the second polyolefin film web may contain one or more polyolefin films, such as LDPE, LLDPE, and mixtures thereof.
[0044] In one preferred embodiment, the second polyolefin film web may include, for example, a polyethylene film web that is bonded to the first web via an adhesive.
[0045] In another preferred embodiment, the second film web is a multilayer structure comprising one or more layers of HDPE, LLDPE, and LDPE as described in U.S. Patent No. 9,421,743.
[0046] In yet another preferred embodiment, the second film web is a multilayer structure in which one layer is an EVOH or nylon layer, as described in U.S. Patent No. 10,300,686.
[0047] In yet another preferred embodiment, the second film web has a metallized layer laminated on the first film web.
[0048] In yet another preferred embodiment, the second film web outer layer has a seal initiation temperature in the range of 75°C to 100°C.
[0049] The thickness of the second polyolefin film layer used to form the recyclable laminate of the present invention may be, for example, 10 μm to 150 μm in one embodiment, 15 μm to 100 μm in another embodiment, and 20 μm to 50 μm in yet another embodiment.
[0050] The layers of the laminating adhesive composition, which is component (iii), are used to bond the first and second layers, which are components (i) and (ii), respectively. The laminating adhesive is pre-used to bond the first and second layers together and can be advantageously recycled after forming a cured laminated structure. When articles, such as packaging articles, are manufactured from a laminated structure containing the laminating adhesive composition, the laminating adhesive composition imparts acceptable recyclability to the packaging articles made from the recyclable laminated structure, enabling the packaging articles to be recycled after use.
[0051] Examples of solvent-based lamination adhesive compositions useful in the present invention include isocyanate-cured polyester materials. In one preferred embodiment, the adhesive from the polyester polyol includes components that provide better compatibility with polyethylene and isocyanate crosslinking agents. Examples of components that provide better compatibility with polyethylene include sebacic acid, azelaic acid, and adipic acid, which react with diols such as hexanediol, octanediol, and any diol having more than 6 but less than 18 carbon atoms, as well as mixtures thereof. The molecular weight of the polyester is less than 90,000 in one embodiment, less than 80,000 in another embodiment, and more than 50,000 in yet another embodiment. The adhesives of the present invention are useful in products such as fresh and frozen foods, and general snack packaging.
[0052] The thickness / weight of the adhesive layer used to bond the first and second film webs and form the multilayer laminated structure of the present invention may be, for example, 2 μm to 5 μm in one common embodiment. Any adhesive weight less than 2 μm or greater than 5 μm may cause adhesion problems and lead to breakage during the rest of the processing.
[0053] The adhesive coating weight of the adhesive layer can range from 1.62 gsm to a maximum of 6 gsm in one common embodiment. Any adhesive weight less than 1.62 gsm or more than 6 gsm may cause adhesion problems and lead to breakage during the rest of the conversion process.
[0054] The adhesion value or adhesive strength of the adhesive 60 minutes (min) after lamination may depend on the polyolefin film layer of the laminated structure. For example, a laminate having a PE layer may have an adhesion value of more than 50 grams per 15 millimeters (g / 15mm) in one embodiment, more than 150 g / 15mm in another embodiment, more than 500 g / 15mm in yet another embodiment, and more than 1,000 g / 15mm in yet another embodiment, accompanied by a failure mode of film tearing. In one preferred embodiment, the adhesive strength of the adhesive of the present invention is, for example, 50 g / 15mm to 2,000 g / 15mm.
[0055] The adhesive useful in the present invention has several other beneficial properties compared to other known laminating adhesives, for example, the adhesive has superior performance in terms of transparency and runnability on laminating equipment.
[0056] The laminated structure of the present invention may include, in addition to the above-mentioned component layers (i) to (iii), other optional layered substrates, component (iv). For example, if desired, substrates such as EVOH, PVDC, OPA, and mixtures thereof can be laminated (bonded) to the above-mentioned first and second layers.
[0057] In one general embodiment, the multilayer laminate of the present invention is, for example, (I) A step of providing the above-mentioned (i) first film substrate, (ii) second woven fabric substrate, and (iii) adhesive composition, (II) A step of applying the adhesive composition to at least a portion of the surface of the first or second substrate (also known as the "carrier web") to form an adhesive layer on the surface of the first or second film substrate, (III) A step of combining the first and second film substrates together with the adhesive layer by bringing the adhesive-coated film substrate into contact with each of the first and second film substrates together with the adhesive, so as to be sufficient to form a laminate layer disposed between the first and second substrates; (IV) The structure of step (III) is produced by a process that includes curing the adhesive composition, for example at room temperature (approximately 25°C) or a high temperature, to bond the two film substrates together and form a multilayer laminate.
[0058] The application of the adhesive composition can be carried out by conventional means known in the art for applying the adhesive composition or formulation to a film substrate. For example, the adhesive composition can be applied using conventional lamination apparatus and processes, which include applying the adhesive using a rotogravia lamination apparatus having oven drying capabilities.
[0059] In addition to the recyclability properties imparted to the multilayer laminate produced according to the process described above, other advantageous properties exhibited by the resulting multilayer laminate may include, for example, a laminate having substantially cloud-free properties. For example, MDO PE and BOPE films can have a turbidity value of less than 8%, while standard inflation films are typically higher than 8%. In one embodiment, the multilayer laminate of the present invention generally has a turbidity value of 6% to 50%. In another embodiment, the multilayer laminate generally has a turbidity value of 10% to 40%.
[0060] In general, the laminates of the present invention can be used in a wide range of applications before recycling, for example, in packaging applications for manufacturing various packaging materials and products. For example, the laminates can be used in bulk packaging of edible grains / legumes, seed packaging, lentil and cereal packaging, fertilizer packaging, oilseed packaging, sugar packaging, salt packaging, pharmaceutical packaging, other food packaging, and personal care items such as bath salts and detergent pods. The film can also be used as packaging material for baby wipes, feminine hygiene products, cereal bars, protein bars, cheese and confectionery products. When used in heavy-duty packaging of edible grains / legumes, the packaged articles will not show any signs of tunneling / delamination / deformation in the laminate after the adhesive has cured for 24 hours (hr). Other advantageous features and applications of the recyclable laminates when used to package articles include, for example, resistance to harsh weather conditions, high tensile strength, robust drop test resistance, excellent optical appearance, and resistance to leakage. The recycled materials of the present invention can also be used to regenerate non-packaging materials.
[0061] One of the advantages of the present invention is that used virgin articles (first articles) made from the laminate of the present invention can be processed, that is, processed by a recycling process. After recycling, recycled materials from the first virgin article can be used to produce subsequent recycled laminates, and thus recycled articles (i.e., second articles), which have properties and performance very similar to the first virgin article. One object of the present invention is to produce second articles that function as well as, or better than, the first article, that is, the properties of the second article are 100% the same as or better than those of the first article. At a minimum, the properties of the second article are maintained at a performance level sufficient to provide a second article that is useful for a different application.
[0062] For example, a new single-layer film structure (second article) made using recycled material from a recycled article (first article) may have properties that show a performance degradation of <40% compared to a control film that is reprocessed in the same manner as a virgin article and has no adhesives added. In some embodiments, the new single-layer film structure (second article) may have properties that show a performance degradation of <40% in one embodiment, <30% in another embodiment, <25% in yet another embodiment, and <15% in yet another embodiment. In some embodiments, the new single-layer film structure may have properties that show a performance degradation in the range of 0% to <40% in one embodiment, 0.01% to <40% in another embodiment, and 0.1% to <40% in yet another embodiment. In some embodiments, the new single-layer film structure may have properties that show a performance degradation in the range of 0% to <25% in one embodiment, 0.01% to <25% in another embodiment, and 0.1% to <25% in yet another embodiment. In some embodiments, the new single-layer film structure may have properties that exhibit a degradation in performance in the range of 0% to <10% in one embodiment, 0.01% to <10% in another embodiment, and 0.1% to <10% in yet another embodiment.
[0063] In a typical embodiment, for example, a process for producing a reprocessed second article from a first packaged article (i.e., a virgin article) includes the steps of (A) providing a first packaged article made from the laminate of the present invention, (B) fragmenting the packaged article from step (A) to produce a plurality of fragments of a predetermined size, (C) pelletizing the plurality of fragments from step (B) to form a plurality of pellets of a predetermined size, and (D) processing the pellets from step (C) to form a reprocessed second article.
[0064] In some embodiments, the third article can be produced from a reprocessed second article made by the general process described above. For example, the third article can be selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products. The present specification includes the following embodiments. Section 1: A first article having recyclable properties, (a) at least one polyolefin polymer, (b) A solvent-based adhesive composition having recyclable properties, wherein the recyclable properties of the solvent-based adhesive composition are such that when a first article having the solvent-based adhesive composition is reworked, the first article having the solvent-based adhesive composition exhibits a performance degradation of less than 40 percent compared to a control article without the solvent-based adhesive composition that is reworked in the same manner as the first article having the solvent-based adhesive composition. Section 2: The first article according to item 1, wherein the polyolefin polymer is polyethylene. Section 3: The first article according to item 1, wherein the solvent-based adhesive composition is an acrylic adhesive composition. Section 4: The first article according to claim 3, wherein the acrylic adhesive comprises a water-dispersible acrylate crosslinking agent, an isocyanate crosslinking agent, and a mixture thereof. Section 5: The first article according to claim 1, wherein the first article is selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products. Item 6: A second article made from any one of the first articles described in item 5. Section 7: The second article according to claim 6, wherein the second article is selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products. Section 8: A process for producing a first article having recyclable properties, (a) at least one polyolefin polymer, (b) A solvent-based adhesive composition having recyclable properties, wherein the recyclable properties of the solvent-based adhesive composition are such that when a first article having the solvent-based adhesive composition is reworked, the first article having the solvent-based adhesive composition exhibits a performance degradation of less than 40 percent compared to a control article without the solvent-based adhesive composition that is reworked in the same manner as the first article having the solvent-based adhesive composition. Section 9: A film structure having recyclable properties, (α) at least one first polymer film layer, (β) At least one layer of a solvent-based adhesive composition having recyclable properties, wherein the recyclable properties of the solvent-based adhesive composition are such that when a film structure having the solvent-based adhesive composition is reprocessed, the film structure having the solvent-based adhesive composition exhibits a performance degradation of less than 40 percent compared to a control structure without the solvent-based adhesive composition that is reprocessed in the same manner as the film structure having the solvent-based adhesive composition, A film structure wherein the solvent-based adhesive composition is compatible with the at least one first polymer film layer, and at least one layer of the solvent-based adhesive composition is disposed on the surface of the at least one first polymer film layer. Section 10: A multilayer laminated structure having recyclable properties, (i) at least one first polymer film layer, (ii) at least one second polymer film layer, (iii) at least one layer of a solvent-based adhesive composition having recyclability, wherein the recyclability of the solvent-based adhesive composition is such that when a multilayer laminate having the solvent-based adhesive composition is reworked, the multilayer laminate having the solvent-based adhesive composition exhibits a performance degradation of less than 25 percent compared to a control structure without the solvent-based adhesive composition that is reworked in the same manner as the multilayer laminate having the solvent-based adhesive composition, A multilayer laminated structure wherein the solvent-based adhesive composition is compatible with the at least one first film layer and the at least one second film layer, and at least one layer of the solvent-based adhesive composition is disposed on the surface of at least one of the at least one first film layer and the at least one second film layer in order to bond the at least one first film layer and the at least one second film layer together. Section 11: A process for generating a multilayer laminated structure, (I) A step of providing (i) at least one first polymer film layer, (ii) at least one second polymer film layer, and (iii) a solvent-based adhesive composition compatible with the first film layer and the second film layer for bonding the first film layer to the second film layer, wherein the solvent-based adhesive composition has recyclability, and the recyclability of the solvent-based adhesive composition is such that when a multilayer laminate having the solvent-based adhesive composition is reprocessed, the multilayer laminate having the solvent-based adhesive composition shows a performance degradation of less than 30 percent compared to a control structure without the solvent-based adhesive composition that is reprocessed in the same manner as a multilayer laminate having the solvent-based adhesive composition. (II) A step of applying the solvent-based adhesive composition from step (I) to at least a portion of the surface of at least one of the first film layer and the second film layer from step (I) to form a layer of the solvent-based adhesive composition disposed between the first film layer and the second film layer in order to bond the first film layer and the second film layer together, (III) A step of combining the first film layer and the second film layer together with a layer of the solvent-based adhesive composition sufficient to form a multilayer laminated structure, A process comprising (IV) curing the multilayer laminated structure of step (III) to form a cured laminate. Section 12: A packaging article made from a multilayer laminated structure as described in item 10. Section 13: A process for producing a reprocessed second article from the packaged article described in item 12, (A) The process of providing the packaged article as described in item 12, (B) A step of fragmenting the packaged article from step (A) to generate a number of fragments of a predetermined size, (C) A step of pelletizing the plurality of fragments from step (B) to form a plurality of pellets of a predetermined size, A process comprising (D) processing the plurality of pellets from step (C) to form a reprocessed second article. Section 14: A third article produced from the second article that has been reworked as described in item 13. Section 15: The third article according to claim 14, wherein the third article is selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products. [Examples]
[0065] The following embodiments are provided to illustrate the invention in further detail, but should not be construed as limiting the scope of the claims. Unless otherwise indicated, all parts and percentages are by weight.
[0066] Table I describes the various materials used in the examples (Inv.Ex.) and comparative examples (Comp.Ex.) of the present invention. [Table 1]
[0067] General procedures for film production The sealant web film described in Table II, Sealant Web Film Structures, and the printed web film described in Table III, Printed Web Film Structures, were produced with seven layers, the composition of each of the seven layers being described in Tables II and III, respectively. The films were produced using the following general process. Each film was made on a seven-layer inflation film line (available from Hosokawa-Alpine). The line utilizes seven 50 mm diameter 30 L / D extruders feeding to a 250 mm diameter spiral mandrel die with a 2 mm die gap. The output speed was 148 kilograms per hour (kg / hr), and the melting temperatures were 240°C to 245°C for layers 1-6 and 185°C to 200°C for layer 7. A blow-up ratio of 2.5 was used when blowing the film, and the film was cooled with single-lip air ring and internal bubble cooling. The line speed was approximately 17 meters per minute (m / min), and the film was corona-treated to achieve an average surface energy of 43 dynes / centimeter. [Table 2] [Table 3]
[0068] After producing two separate rolls of the two films described above (sealant web film and printed web film), a first set of the two films is laminated with the aqueous adhesive composition of the present invention, and a second set of the two films is laminated with a conventional polyurethane laminating adhesive, using the process "General procedure for film lamination" described below herein.
[0069] Each of the resulting composite film laminates is reprocessed by shredding the film, pelletizing the film, extruding / compounding the pellets, and forming a second film from the compounded pellets derived from each of the first composite film laminates, using the procedure described below herein.
[0070] Next, the second film was tested using the test procedure described below, and the test results are recorded in Tables VI and VII.
[0071] General procedure for film lamination Lamination is achieved using a commercially available Super-Combi3000 series laminator (available from Nordmeccanica). The laminator has a maximum film width of 1,320 mm and a minimum film width of 600 mm. In addition, the laminator includes two modular coating decks: (1) an aqueous deck for aqueous lamination, and (2) a gravure deck for aqueous and solvent-based adhesives / coatings. The laminator also includes a two-zone forced-air dryer and a 7.5 kilowatt (KW) corona treatment device (available from Enercon Industries Corporation) for both primary and secondary films. The maximum line speed of the laminator is 400 meters per minute (m / min) or 1,312 feet per minute (ft / min). All unwinding uses 76 mm or 152 mm cores, and unwinding uses only 152 mm cores. The laminator can run most packaging films, including polyester, oriented polypropylene, polyethylene, nylon, paper, and foil (secondary only). For the purposes of the present invention, the solvent-based laminating adhesive used in the examples was ADCOTE® 102E (available from The Dow Chemical Company), and the film and adhesive were run on the laminator using the laminator's gravure deck with a target coating of 2.4 gsm. After lamination was complete, the roll of film was allowed to fully cure at room temperature for 7 days.
[0072] General procedure for film shredding / pelletization Shredding and pelletizing are achieved using the INTAREMA® 605K pelletizer unit (available from EREMA). The pelletizer barrel zone is run at 171°C, and the pelletizer zone is run at 176°C.
[0073] General procedure for determining blend ratios The pellets produced using the above pelletizer are compounded using a LabTech 26mm twin-screw extruder, type LTE26-44 (Part II). The operating parameters of the above extruder are listed in Table IV. [Table 4]
[0074] manufacturing line The blend is produced using six Movacolor gravimetric feeders connected by vibrating trays that feed into a 20mm twin-screw extruder (available from LabTech Engineering Company LTD ["LabTech"]). Two mixing zones ensure a consistent composition at the extruder outlet. Downstream of the extruder, 3.0 cubic centimeters per revolution (cm) 3 A gear pump is present, which provides high steady pressure for extruding the material through the inflation film die. A standard 5.08 cm (2 inch) diameter cylindrical spiral mandrel die (LabTech) has six spiral channels and a 1.0 mm die gap. Pressurized air inflates the film bubbles to a blow-up ratio (BUR) of 2.5 to 4 BUR (where "BUR" is defined as the maximum bubble diameter divided by the die diameter). A dual-lip air ring driven by a variable-speed blower (Labtech) is used in all experiments. The frost line height (FLH) can be varied from 127 mm to 330 mm and is controlled by changing the blower speed and air ring chimney. By adjusting the nip roller speed, the film thickness is typically controlled within ±10%. The lay flat is trimmed to a width of 150 mm (6 inch) and rolled onto two rolls. Standard and possible condition ranges are summarized in Table V. [Table 5]
[0075] Film testing The films prepared in the examples were tested for physical properties: dart, tear, secant coefficient, and tensile strength. The tests were performed as described in the following ASTM test methods: drop dart was measured using ASTM D1709; Elmendorf tear was measured using ASTM D1922; secant coefficient was measured using ASTM D882; tensile strength was measured using ASTM D822; and turbidity was measured using ASTM D1003.
[0076] Examples 1-3 and Comparative Examples A-D Tables VI and VII provide the results of testing the films of the present invention (Inv.Ex.1-3) against a control film (Comp.Ex.A). The reprocessed control film consists of a 1:1 blend of printed web and sealant web film and does not contain lamination adhesive. The sample control film is a sample against which all laminated films are compared.
[0077] All the laminated films were laminated onto a printed web and a sealant web to produce a single resulting film. This resulting film was then shredded, pelletized, and blended with control pellets prepared from a control film in various ratios.
[0078] The film parameters included the film thickness of each of the Inv.Ex.1-3 and Comp.Ex.A-D films, which was 2 mil ± 0.5 mil or less. All other properties of the Inv.Ex.1-3 films could not show a performance degradation of more than 40% compared to the control film sample.
[0079] Another lamination adhesive used as a comparative sample was Adcote® 577, which was used for the film samples in Comparative Examples B to D.
[0080] result Each of the tested adhesive compositions of the present invention (Table VI, Inv.Ex.1-3) is a solvent-based lamination adhesive, ADCOTE® 102E. The results shown in Table VI indicate that the adhesive compositions of the present invention pass the "<30% performance degradation change" test in all categories shown in Table VI, for example. For example, the dirt performance is well within the performance limit of a performance degradation change of 40% or more compared to the performance of Comp.Ex.A. When pellets containing the adhesive compositions of the present invention are used in amounts of 10% to 50%, the adhesive compositions of the present invention were determined to pass the recyclability test.
[0081] Two solvent system samples containing the lamination adhesive ADCOTE® 577 / CR87-124 were tested as shown in Table VII. The lamination adhesives used in Comp.Ex.B-D are highly crosslinked PU-based. The Comp.Ex.B-D samples failed the dirt test with a performance degradation of more than 40% (see Table VII, Comp.Ex.B-D). It is theorized that this is likely due to the stiffness imparted by the highly crosslinked adhesive material in Comp.Ex.B-D. A dirt drop of more than 40% at concentrations of 10%-50% results in the Comp.Ex.B-D adhesives failing to meet the recyclability criteria. [Table 6] [Table 7]
Claims
1. A first article having recyclable properties, (a) at least one polyolefin polymer, (b) A combination of a solvent-based polyester adhesive composition having recyclable properties, The recycling properties of the solvent-based polyester adhesive composition are such that, when the first article is reprocessed, the reprocessed first article shows a reduction of 40 percent or less in terms of drop dirt compared to a control article that is reprocessed in the same manner as the first article but differs only in that it does not have the solvent-based polyester adhesive composition.
2. The first article according to claim 1, wherein the polyolefin polymer is polyethylene.
3. The first article according to claim 1, wherein the first article is selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products.
4. A second article made from any one of the first articles described in claim 3.
5. The second article according to claim 4, wherein the second article is selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products.
6. A process for producing a first article having recyclable properties, (a) at least one polyolefin polymer, (b) A step of bringing together a solvent-based polyester adhesive composition having recyclable properties, The recycling characteristics of the solvent-based polyester adhesive composition are such that, when the first article is reprocessed, the reprocessed first article shows a reduction of 40 percent or less in terms of drop dirt compared to a control article that is reprocessed in the same manner as the first article but differs only in that it does not have the solvent-based polyester adhesive composition.
7. A film structure having recyclable properties, (α) at least one first polyolefin polymer film layer, (β) comprising at least one layer of a solvent-based polyester adhesive composition having recyclable properties, The recycling characteristics of the solvent-based polyester adhesive composition are such that, when the film structure is reprocessed, the reprocessed film structure shows a reduction of 40 percent or less in terms of falling dirt compared to a control structure that is reprocessed in the same manner as the film structure but differs only in that it does not have the solvent-based polyester adhesive composition. The solvent-based polyester adhesive composition is compatible with the at least one first film layer. A film structure in which at least one layer of the solvent-based polyester adhesive composition is disposed on the surface of the at least one first film layer.
8. A multilayer laminated structure having recyclable properties, (i) at least one first polyolefin polymer film layer, (ii) at least one second polyolefin polymer film layer, (iii) comprising at least one layer of a solvent-based polyester adhesive composition having recyclable properties, The recycling characteristics of the solvent-based polyester adhesive composition are such that, when the multilayer laminated structure is reprocessed, the reprocessed multilayer laminated structure shows a reduction of less than 25 percent in terms of drop dirt compared to a control structure that is reprocessed in the same manner as the multilayer laminated structure but differs only in that it does not have the solvent-based polyester adhesive composition. The solvent-based polyester adhesive composition is compatible with the at least one first film layer and the at least one second film layer. A multilayer laminated structure in which at least one layer of the solvent-based polyester adhesive composition is disposed on the surface of at least one of the at least one first film layer and the at least one second film layer in order to bond the at least one first film layer and the at least one second film layer together.
9. A process for generating a multilayer laminated structure, (I) (i) at least one first polyolefin polymer film layer, (ii) at least one second polyolefin polymer film layer, and (iii) at least one layer of a solvent-based polyester adhesive composition having recyclable properties and being compatible with the first film layer and the second film layer, for bonding the first film layer to the second film layer, The recycling characteristics of the solvent-based polyester adhesive composition are such that, when the multilayer laminated structure is reprocessed, the reprocessed multilayer laminated structure shows a reduction of less than 30 percent in terms of drop dirt compared to a control structure that is reprocessed in the same manner as the multilayer laminated structure but differs only in that it does not have the solvent-based polyester adhesive composition, in step (I). (II) Step (II) is to apply the solvent-based polyester adhesive composition from step (I) to at least a portion of the surface of at least one of the first film layer and the second film layer from step (I) to form a layer of the solvent-based polyester adhesive composition disposed between the first film layer and the second film layer in order to bond the first film layer and the second film layer together. (III) A step of combining the first film layer and the second film layer together with the solvent-based polyester adhesive composition layer so as to be sufficient to form the multilayer laminated structure (III), A process comprising: (IV) a step (IV) of curing the multilayer laminated structure of step (III).
10. A process for producing a packaged article, comprising the steps of: providing a multilayer laminated structure produced by the process described in claim 9; and producing a packaged article from the multilayer laminated structure.
11. A process for producing a reprocessed second article from a packaged article produced by the process described in claim 10, (A) A step of providing a packaged article manufactured by the process described in claim 10, (B) A step of fragmenting the packaged article from step (A) to generate a number of fragments of a predetermined size, (C) A step of pelletizing the plurality of fragments from step (B) to form a plurality of pellets of a predetermined size, A process comprising (D) processing the plurality of pellets from step (C) to form a reprocessed second article.
12. A process for producing a third article, comprising the steps of: providing the reworked second article produced by the process described in claim 11; and producing a third article from the reworked second article.
13. The process according to claim 12, wherein the third article is selected from the group consisting of pellets, single-layer or multi-layer films, multi-layer laminates, and packaging materials or products.
Citation Information
Patent Citations
Acrylic polymer composition, method for manufacturing the same and tacky adhesive composition containing the acrylic polymer composition
JP2002012604A
Adhesive for cold drawn lamination without bisphenol-a
JP2018502935A
All-polyethylene laminate film construction with barrier adhesive layer
JP2020529935A
JPP6716764B
Method for separating and recovering layered film
WO2020059516A1